Effects of Resveratrol Co-Administration on Celecoxib Disposition and Pharmacokinetics in Healthy Volunteers - Helal, Nagwa I.; El-Khodary, Noha M.; Omran, Gamal A.; El-Masry, Soha M. (Drug Research, 2023)
The objective of the current study was to investigate the effects of resveratrol (RSV), a natural herbal remedy used as an adjacent anti-inflammatory supplement on, the pharmacokinetics of celecoxib in healthy male volunteers. Twelve healthy human participants were involved in two-period open-labeled trial. Celecoxib (200 mg) was given as a single oral dose under fasting conditions as a control phase. Afterward, RSV (500 mg) commenced as a single oral dose for ten days as a treatment phase. Blood samples were collected during the control and treatment phases and analyzed using the validated High-performance liquid chromatography (HPLC) method. RSV pre-exposure significantly increased the area under the curve (AUC0–24), peak plasma concentration (Cmax), absorption rate constant (ka), and prolongated half-life (t1/2), along with a decrease in elimination rate constant (ke). Meanwhile, the volume of distribution (Vd/F) and apparent total body clearance (CL/F) were significantly decreased for celecoxib. There was no significant change in the time it takes for celecoxib to reach the maximum concentration (tmax) was observed. The obtained results suggested the presence of a beneficial pharmacokinetic interaction between RSV and celecoxib. Consequently, combining resveratrol as an herbal remedy and celecoxib as an anti-inflammatory drug may synergistically reduce inflammation and osteoarthritis with minimal side effects.
Keywords: Resveratrol; celecoxib; P-glycoprotein; CYP2C9; CYP3A4; pharmacokinetic interactions